Celery powder drink as an alternative treatment for hypertension - Sabella Vania Simon; Saifuddin Sirajuddin; Abdul Salam (CORE JOURNAL, 2021)
Celery is a herbal plant often used to lower blood pressure because some of the compounds in this plant has a role as an anti-hypertension and the side effect is quite minor. The freshness of celery plant only lasts for 8 to 12 hours after being harvested, so it needs to be developed into a ready-to-drink beverage product such as a powder drink. The purpose of this study was to determine the formulation, antioxidant profile and shelf life of celery-based powder drink. This study is laboratory based descriptive. Celery-based powder drink was screened for its possible antioxidant compounds such as alkaloids, flavonoids, phenolic, triterpenoid, steroids, and saponins. The DPPH assay is used to analyze antioxidant activities. ASLT method with Arrhenius design is used to determine the shelf life of celery-based powder drink. The changes in the quality of the product were being observed for 14 days in 3 different storage temperature. Results: The antioxidant screening tests show the presence of alkaloids, flavonoids, phenolic, triterpenoid, steroids, and saponins in celery-based powder drink. Moreover, this sample showed the high antioxidant activities with the IC50 value of 70,74 ppm. The shelf life of celery-based powder drink can not be calculated because the water content of the sample is higher than SNI standards. Celery based powder drink contain antioxidants and showed the high antioxidant activities. Drying process needs to be done using other methods to produce better quality of powder drinks.